BIOMECHANICAL MODEL OF THE SPRINT START - Milan Čoh (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
The study analysed and identifi ed the major kinematic parameters of the phases of sprint start and block acceleration that infl uence the results of sprint running. The biomechanical measurements and kinematic analysis were performed on the best world's best sprinters during his preparation for the European Athletics Championship in Geteborg 2006. In this competition Matic Osovnikar won the bronze medal in a 100- metre run set the Slovenian national record with 10.14 s. The kinematic parameters of the sprint start were established on the basis of a 2-D kinematic analysis, using a high-speed camera with a frequency of 200 F/s. The measurements of block acceleration were made by means of the OPTO TRACK technology and an infra-red photo cell system. The athlete performed fi ve, 20m low-start sprints in constant and controlled measurement conditions. The subject of the study was the set position from the point of view of the height of the total body centre of gravity (TBCG), the block time at the front and rear blocks, block velocity, the block face angle, the velocity of the TBCG in the fi rst three metres and the kinematic parameters of block acceleration in the fi rst ten steps. The study showed the following were the key performance factors in the two phases of sprint running: medium start block distance, block velocity, low block face angles, fi rst step length, low vertical rise in the TBCG in the fi rst three metres of block acceleration, contact phase/fl ight phase index in the fi rst ten steps and the optimal ratio between the length and frequency of steps.